Action Research in Information System and Internal Auditing Research - Rustendi, Tedi -; Asyaky, Muhammad Sidik (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2025)
Action research is a research design that has the potential to be used in information systems and internal auditing research because of its similarities in the framework. Action research was initially qualitative, but as its methodology developed, quantitative components were added as an integral part of both the data collection and its analysis and interpretation phases. Mixed methods are considered effective in leveraging the strengths and reducing the weaknesses of both quantitative and qualitative approaches in either parallel or sequential designs. The author supports the idea that, methodologically, action research in information systems and internal auditing can adopt mixed methods in either parallel or sequential designs while considering scientific stages and ethical values.Keywords: action research, quantitative, qualitative, mixed methods.